Access of people with pulmonary tuberculosis to government programs: Primary Care professionals' perceptions - Hildegard Soares Barrozo de Lima; Vitória Regina Domingues Sodré; Cleide Aparecida Alves Souza; Mirian Domingos Cardoso; Crhistinne Cavalheiro Maymone Gonçalves; Laura Maria Vidal Nogueira; Ivaneide Leal Ataíde Rodrigues; Erlon Gabriel Rego de Andrade; Alexandre Aguiar Pereira; Maria Catarina Salvador da Motta; Maria Helena do Nascimento Souza; Regina Célia Gollner Zeitoune; et al. (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to analyze Primary Health Care professionals' perceptions about the access of people with pulmonary tuberculosis to government social support and income transfer programs. Methods: multicenter/qualitative study, carried out in Family Health Units in four Brazilian capitals: Belém/Pará, Campo Grande/Mato Grosso do Sul, Recife/Pernambuco and Rio de Janeiro/Rio de Janeiro. Fifty-eight professionals participated (social workers, dentists, nurses, pharmacists, physicians and nursing technicians), who provided assistance to people with pulmonary tuberculosis. Individual interviews were conducted, and the content analysis technique was used. Results: among the participants, 45/77.6% were women and 33/56.9% were between 25 and 40 years old. Two thematic categories were organized, demonstrating the perceptions about the possibilities of access to government programs by people with pulmonary tuberculosis in vulnerable situations and the obstacles inherent to this context. Final considerations: it is necessary to move forward in improving patient access to social programs.